Antifungal prescription practices and consumption in a tertiary care hospital of a developing country. Issue 10 (16th August 2022) - Kaur, Harsimran; Krishnamoorthi, Sivanantham; Dhaliwal, Navneet; Biswal, Manisha; Singh, Shreya; Muthu, Valliappan; Rudramurthy, Shivaprakash M.; Agarwal, Ritesh; Ghoshal, Sushmita; Singh, Surjit; Malhotra, Pankaj; Jain, Sanjay; et al.
Abstract: Background: Antifungal stewardship is a less explored component of antimicrobial stewardship programmes, especially in developing countries. Objective: We aimed to determine antifungal prescription practices in a tertiary centre of a developing country to identify the challenges for antifungal stewardship programmes. Methods: Four single‐day point prevalent surveys were performed in inpatient units and data were collected from medical records. Antifungal use was recorded in terms of consumption, therapeutic strategies and appropriateness. Results: We found a 2.42%‐point prevalence of antifungal prescriptions. Antifungal use was higher in children than adults (4.1% vs. 2.03%), medical than surgical units (3.7% vs. 1.24%) and ICUs than general wards (5.8% vs. 1.9%). The highest antifungal use was observed in the haematology‐oncology units (29.3%) followed by emergency (16.2%) and gastroenterology units (11.6%). Among 215 prescriptions, amphotericin B was the most commonly prescribed (50.2%) followed by fluconazole (31.6%). The targeted antifungal therapy was practised more commonly (31.5%) than empiric (29.1%), pre‐emptive (22.6%) and prophylactic (16.8%) therapy. Amphotericin B was commonly used for pre‐emptive ( p = .001) and targeted ( p = .049) therapy, while fluconazole ( p = .001) and voriconazole ( p = .011) for prophylaxis. The prescriptions were inappropriate in 25.1% due to the wrong choice of antifungal (44.4%), indication (27.7%) and dosage (24%). The overall mean antifungal consumption was 2.71 DDD/1000 PD and 8.96 DOT/1000 PD. Conclusions: We report here the low prevalence of antifungal use at a tertiary care centre in a developing country. Though training for antifungal use would be important for antifungal stewardship, the challenge would remain with the affordability of antifungals.